2021
DOI: 10.1038/s41380-021-01016-1
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the temporal nature of brain GR activity in the NFκB signal transition leading to depressive-like behavior

Abstract: The fine-tuning of neuroinflammation is crucial for brain homeostasis as well as its immune response. The transcription factor, nuclear factor-κ-B (NFκB) is a key inflammatory player that is antagonized via anti-inflammatory actions exerted by the glucocorticoid receptor (GR). However, technical limitations have restricted our understanding of how GR is involved in the dynamics of NFκB in vivo. In this study, we used an improved lentiviral-based reporter to elucidate the time course of NFκB and GR activities d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Persistent chronic stress abnormally activates the HPA axis, which is an important factor in the development of chronic inflammatory responses and anxiety. [50][51][52][53] Repeated restraint stress (RRS) model is established by imposing sustained stress response on animals through long-term restraint typically used to stimulate GAD that is accompanied by hypercortisolism and anxiety-like behaviors. 54 In the present study, we established a mouse model of RRS based on previous literature and found that RRS models spent shorter dwell times in the central zones (open field test) and in the open arms (EPM test) than normal mice, as well as exhibited a significant increase in serum corticosterone.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent chronic stress abnormally activates the HPA axis, which is an important factor in the development of chronic inflammatory responses and anxiety. [50][51][52][53] Repeated restraint stress (RRS) model is established by imposing sustained stress response on animals through long-term restraint typically used to stimulate GAD that is accompanied by hypercortisolism and anxiety-like behaviors. 54 In the present study, we established a mouse model of RRS based on previous literature and found that RRS models spent shorter dwell times in the central zones (open field test) and in the open arms (EPM test) than normal mice, as well as exhibited a significant increase in serum corticosterone.…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation the p65:p50 dimer translocate to the nucleus where it binds specific DNA sequences called κB response elements and induce transactivation of target genes (Giridharan & Srinivasan, 2018). In-vivo tracking of activated p65 showed that the expression of κB responsive genes were significantly higher in animals that were challenged during the resting period (GC low) than during the active period (GC high) supporting the circadian influence on NF-κB p65 activation (Han et al, 2021). The profound anti-inflammatory effects of GC are largely attributed to GR mediated inhibition of NF-κB p65, by one of three methods.…”
Section: Interactions Between Gc Clock Components and Nuclear Factor-κbmentioning
confidence: 91%
“…Age related changes in circulating cortisol have been variably reported in humans, with many studies suggesting higher plasma cortisol concentrations in older individuals ( Echouffo-Tcheugui et al, 2018 ; Hatfeld et al, 2004 ; Pietrzak et al, 2017 ). The discrepancies in observations could be attributed to the methods of assessment and the number and frequency of samples assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin 1β (IL‐1β) increased in the brain of mice when exposed to a startle stimulus 45 . Peripheral administration of the same cytokine attenuated the startle response through its activity on the adrenal gland leading to the release of glucocorticoids, which have anti‐inflammatory properties 46,47 . Indeed, the startle response led to an increase in corticosterone expression in rats 48 .…”
Section: Little Is Known Of Neutrophil Involvement In the Acquisition...mentioning
confidence: 99%